A failure of nerve : leadership in the age of the quick fix - Friedman, Edwin H.; Treadwell, Margaret M.; Beal, Edward W. (New York : Seabury Books, 2007)
Friedman's insights about our regressed, "seatbelt society," oriented toward safety rather than adventure, help explain the sabotage that leaders constantly face today. Suspicious of the "quick fixes" and instant solutions that sweep through our culture only to give way to the next fad, he argues for strength and self-differentiation as the marks of true leadership. His formula for success is more maturity, not more data; stamina, not technique; and personal responsibility, not empathy. This book was unfinished at the time of Friedman's death, and originally published in a limited edition. This new edition makes his life-changing insights and challenges to a new generation of readers.
Introduction: the problem with leadership -- Imaginative gridlock and the spirit of adventure -- A society in regression -- Data junkyards and data junkies : the fallacy of expertise -- Survival in a hostile environment : the fallacy of empathy -- Autocracy versus integrity : the fallacies of self -- Take five -- Emotional triangles -- Crisis and sabotage : the keys to the kingdom -- Epilogue: the presence of the past.
Includes bibliographical references and index.
Keywords: Leadership